A cold peace : - Garten, Jeffrey E. (Times Books, 1992)
This book consists of the following many parts: challenging old assumptions, Germany and japan in the American mind, different historical legacies, different kinds of capitalism, open vs closed societies, dividing up the world, the leadership vacuum, America in the American mind.